Humanist Literacy in Critical Reading Activities as an Alternative Direction for Future Language Learning - Asnawi Asnawi; Ida Zulaeha; Sri Wahyuni; Fauzul Etfita (STAI Hubbulwathan Duri, 2022)
Humanist literacy is an awareness of reading and understanding human phenomena that can be created through critical reading activities. Critical reading activities aim to reflect on the reading results so that they can make wise decisions on how to think and behave humanely. Decision-making skills need to be improved through critical reading learning with a humanist literacy approach. The problem so far is the unavailability of future learning designs by integrating humanist literacy through critical reading activities. Therefore, this study focuses on how to integrate humanist literacy in critical reading activities as an alternative direction for future language learning. The purpose of this study was to describe the grand design of integrating humanist literacy in critical reading activities as an alternative direction for future language learning. This research is a development research of one part of the development research procedure. The data for this study were sourced from the comments of lecturers and students from questionnaires distributed online. This research instrument was developed based on the concept of language learning, characteristics of humanist literacy, and characteristics of critical reading that have been validated. Data analysis was carried out critically reflectively by using tagCrow and AntCont applications. The results of the study prove that the grand design of integrating humanist literacy in critical reading activities can be carried out through communicating humanist literacy, collaborating humanist literacy, and humanist critical thinking with sub-skills of analyzing, interpreting, inferring, evaluating, explaining, and regulating oneself in a humanistic manner to make decisions. wisely according to the principles of humanistic life.